Attitudes, behaviours and perceptions of Italian General Practitioner trainees towards influenza vaccination in Western Sicily (Italy) (Italian Journal of Public Health, 2012)
Background: general practitioners (gPs) have to be considered as key figures of health promotionamong health care workers since they are strongly asked to recommend influenza vaccination to theirpatients and perform on them. despite this consideration, gPs have influenza vaccination rates that aresignificantly below the 75% coverage proposed by International Public Health guidelines. In order toincrease future coverage of influenza vaccination within gPs, and through them within the population, theaim of this study was to assess determinants associated with influenza vaccine uptake among gP trainees.MetHods: a survey was carried out on gP trainees attending the training course in community Medicineof Western sicily (Italy). each participant was interviewed via an anonymous self-administered ques-tionnaire which included questions on attitudes, behaviours and perceptions regarding influenza andinfluenza vaccination.results: Vaccination coverage was 26.2% for seasonal 2008-2009 influenza, 20.0% for pandemic a(H1n1) influenza and 18.7% for seasonal 2009-2010 influenza. considering themselves as a high riskgroup for developing influenza was significantly associated with seasonal 2009-2010 influenza vaccine(adj-or 2.35). Vaccination for seasonal 2009-2010 influenza (adj-or 1 063), pandemic a (H1n1) influ-enza (adj-or 16.77) and seasonal 2010-2011 influenza (adj-or 38.08) were significantly more frequentin gP trainees who had been vaccinated more than three times in the previous five influenza seasons.conclusIon: Influenza vaccine uptake among gP trainees is more a habit than a professional respon-sibility, and influenza vaccination is still administrated to patients on the basis of gP trainees’ clinicalevaluation or patient willingness. Multidisciplinary learning pathways may implement vaccinationcoverage in the attempt to modify the current gP trainees’ attitude towards recommended influenzavaccination.
Keywords: Influenza Vaccination; General Practitioner Trainees; Attitudes; Western Sicily